Fundamental Literacy of Cash Waqf and Its Impact on Interest in Waqf Among Students With Religiosity as a Moderating Variable - Ambardi, Ambardi; Aini, Nur; Aminah, Aam (Universitas Alma Ata, 2023)
The purpose of this study was to find out whether the cash waqf literacy variable affects students' interest in cash waqf and whether the moderating variable, namely religiosity, will strengthen or weaken the influence of the relationship between literacy variables on student interest in waqf variables. This research was conducted on students of the Ahmad Dahlan Institute of Technology and Business. The sample used in this study was students of the Ahmad Dahlan Jakarta Institute of Technology and Business who were still actively studying. The sampling technique of this study used a nonprobability sampling technique. The number of samples used in this study was 200 respondents. The analysis technique used in this study is the Moderated Regression Analysis, which is an application of multiple linear regression where the equation contains an element of interaction (multiplication of two/more independent variables). From the results of this study, it can be concluded that cash waqf literacy has a positive effect on interest in cash waqf among students. Furthermore, religiosity moderates the relationship between cash waqf literacy and interest in cash waqf. In other words, the religiosity variable can strengthen the relationship between cash waqf literacy and interest in cash waqf among students.